A survey on the analysis and control of evolutionary matrix games. (2018) - Riehl, James; Ramazi, Pouria; Cao, Ming
Abstract: In support of the growing interest in how to efficiently influence complex systems of interacting self-interested agents, we present this review of fundamental concepts, emerging research, and open problems related to the analysis and control of evolutionary matrix games, with particular emphasis on applications in social, economic, and biological networks.